TANGGAPAN PERTUNASAN EMPAT VARIETAS LOKAL, SUKUN TERHADAP PEMANGKASAN DAN PEMUPUKAN NPK - Dedi Setiadi; Hamdan Adma Adinugraha (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
The Study was conducted to examine the sprouting response of four local varieties of bread-fruit to pruning and application of NPK fertilizer. Four local varieties of bread-fruit namely from bone, Banten, Sukabumi and Kediri. The experiment lay out was Randomimized Complete Design with 3 treatment factors. The result did not show significant difference among local varieties. However there are significant differences in budding response . For number of buds. Best treatment was fertilization 20 g and pruning at 50 cm. For buds growth, best treatment was NPK of 30-50 g, and best pruning at 20 and for bud diameter the best NPK dosage was 20 g.